Regulation of proliferation, migration, invasion, and apoptosis in LPS-induced fibroblast-like synoviocytes by astragalus polysaccharide via the EGFR/MAPK signaling pathway (Bangladesh Journal of Pharmacology, 2025)
This study investigated the effects of astragalus polysaccharides on prolifer-ation, apoptosis, migration, invasion, and epidermal growth factor receptor (EGFR)/mitogen-activated protein kinase (MAPK) signaling pathway in human rheumatoid arthritis fibroblast-like synoviocytes (MH7A cells). MH7A cells were randomly divided into control, lipopolysaccharide (LPS), and astragalus polysaccharides (50, 100, and 200 μg/mL) groups for experimental investigation. Cell viability significantly decreased when the concentration of Astragalus polysaccharides exceeded 200 µg/ML; therefore, a dose ≤200 µg/mL was selected for subsequent experiments (p